The Microabrasion Technique with Acrylic Bur. Case Report - Feregrino-Vejar DDS, Lourdes; Gutiérrez-Rojo DDS, Jaime Fabián; Rivas-Gutiérrez DDS, Rafael (Odovtos - International Journal of Dental Sciences, 2016)
Introduction: Some important factors for establishing social interactions seem to be the physical attractiveness and facial appearance, and dental color is one of the most important characteristics correlated with the aesthetics. The microabrasion is a conservative, atraumatic and non restorative technique that removes a superficial layer of enamel that has some defects of texture or color such as brown or white opacities. Case description: Case 1. A 35 year old female showed generalized TF grade 4 and 5 fluorosis. The enamel microabrasion consisted of 3 applications in the upper teeth and 2 more applications on the central incisors and on the right lateral teeth. Case 2. A 42 year old male presented TF grade 3 and 4 fluorosis. The enamel microabrasion consisted of four applications in the lower teeth and 2 applications on the upper teeth. Discussion: The success of enamel microabrasion depends on the location and depth of the enamel defect. Before treatment, patients should be informed that they may required a bonded composite restoration or a bleaching treatment, because the depth of the enamel discoloration is uncertain.